(untitled) (Portuguese Journal of Family Medicine and General Practice, 2012)
ANTIHISTAMINES IN THE COMMON COLD: A COMMON PRESCRIPTON FOR A COMMON CONDITION Goals: Antihistamines are popular among doctors for treatment of symptoms of the common cold. The aim of this paper is to review the evidence for the effectiveness and safety of antihistamines as the sole treatment for symptoms of the common cold in children and adults. Data sources:Medline, evidence-based medicine internet sites, Index of Portuguese Medical Journals and references of selected articles. Review methods: Clinical guidelines, systematic reviews, and randomized controlled trials (RCT), published between January 1980 and October 2010 were collected using the MeSH terms: antihistamine and common cold. The Strength Of Recommendation Taxonomy (SORT) scale of the American Academy of Family Physicians was used for assigning levels of evidence and the strength of recommendation. Results: Seventy articles were found and seven were selected for this review. These include two guidelines on the management of the common cold that do not recommend antihistamines as a sole treatment option and one Cochrane meta-analysis that found no clinical benefit from the use of antihistamines alone. The results of some studies included suggested an increased risk of sedative effects with the use of first generation antihistamines. The authors of this meta-analysis recommend discontinuing the practice of prescribing these drugs in the common cold (level of evidence 1). Four RCT found that different antihistamines were no more effective than placebo in reducing acute cough. Three studies showed no significant differences in side effects (level of evidence 1). Conclusions: The evidence shows that the use of antihistamines as monotherapy in symptomatic treatment of the common cold is ineffective in children and adults (SOR A). Many trials suggest an increased risk of sedative effects with this therapy (SOR B). Sedation may be confused with prostration that would suggest a worsening of the clinical situation. This may add an unnecessary cost to a common prescription.